Auditoría de gestión y su relación con la optimización de los servicios del registro municipal de la propiedad y mercantil del GAD San Jacinto de Buena Fe. 2012 - 2013. - Loor Cevallos, Egda María (2015)
This work was carried out in the company Municipal Registry of Property and Commercial GAD San Jacinto Buena Fe, and different research methods for the realization of the report were used. It began with the use of questionnaires, then observations, interviews and notes were made; section information was collected, and made a brief but necessary knowledge of the department that generates information for services. With the knowledge gained was reached defining the problem which is to solve the optimization services. Since the identification of the problem was necessary to consult the theory through a complete overhaul, to have knowledge in techniques of service processes within the department and solve the situation identified. Based on the methodology specified in the audit plan; have as initial preliminary diagnosis which made it possible to obtain a general understanding of the entity and the processes that form the audited system. Subsequently, the internal control was assessed, scored risk and audit approach was established. In the second stage audit tests applied, using procedures based on the results of the evaluation of internal control, obtaining sufficient, competent and relevant evidence to support the findings. In the final stage is provided comments, conclusions and recommendations for improving the services of the Municipal Registry of Property and Commercial GAD San Jacinto Buena Fe.